GNU Autoconf, Automake, and Libtool - Tromey, Tom; Ellison, Ben; Taylor, Ian Lance; Vaughn, Gary V. (Sams, 2000)
If you are a developer and are looking to participate in the Open Source development growth area you will need to learn new Open Source tools. GNU autoconf, GNU automake and GNU libtool are key tools for Open Source application development. These tools are not easy to learn, so some of the leading authorities on these tools have agreed to work together on this book to teach developers how to boost their productivity and the portability of their application. This book place New Riders/MTP at the center of the Open Source development community. Autoconf, Automake and Libtool is an efficient discourse on the use of autoconf, automake and libtool aimed at reducing the steep learning curve normally associated with these tools. This is a study guide to the interactions between the tools, and how best to get them to cooperate. If you are a developer and have no GNU build environment expertise, this book will help you develop these tools completely and confidently.
Keywords: Operating systems (Computers); Systèmes d'exploitation (Ordinateurs); operating systems